Study of the Assembly of Vesicular Stomatitis Virus N Protein: Role of the P Protein - Green, Todd J. (American Society for Microbiology, 2000)
To derive structural information about the vesicular stomatitis virus (VSV) nucleocapsid (N) protein, the N protein and the VSV phosphoprotein (P protein) were expressed together in Escherichia coli. The N and P proteins formed soluble protein complexes of various molar ratios when coexpressed. The major N/P protein complex was composed of 10 molecules of the N protein, 5 molecules of the P protein, and an RNA. A soluble N protein-RNA oligomer free of the P protein was isolated from the N/P protein-RNA complex using conditions of lowered pH. The molecular weight of the N protein-RNA oligomer, 513,879, as determined by analytical ultracentrifugation, showed that it was composed of 10 molecules of the N protein and an RNA of approximately 90 nucleotides. The N protein-RNA oligomer had the appearance of a disk with outer diameter, inner diameter, and thickness of 148 ± 10 Å, 78 ± 9 Å, and 83 ± 8 Å, respectively, as determined by electron microscopy. RNA in the complexes was protected from RNase digestion and was stable at pH 11. This verified that N/P protein complexes expressed in E. coli were competent for encapsidation. In addition to coexpression with the full-length P protein, the N protein was expressed with the C-terminal 72 amino acids of the P protein. This portion of the P protein was sufficient for binding to the N protein, maintaining it in a soluble state, and for assembly of N protein-RNA oligomers. With the results provided in this report, we propose a model for the assembly of an N/P protein-RNA oligomer.